The benefit of early‐stage diagnosis: A registry‐based survey evaluating the quality of life in patients with melanoma - Jade N. Young; Kelly Griffith‐Bauer; Emma Hill; Emile Latour; Ravikant Samatham; Sancy Leachman (Wiley, 2023)
Abstract Background The morbidity associated with advanced stage melanoma is an important consideration in the dialog surrounding early detection and overdiagnosis. Few studies have stratified melanoma patient quality of life (QoL) by stage at diagnosis. Objective We sought to investigate if melanoma stage is independently associated with changes in QoL within a large, community‐based melanoma registry. Secondarily, we investigated whether demographic factors such as age, geographic location or level of education are associated with changes in QoL in the same population. Methods 1108 melanoma patients were surveyed over a three‐month period using the QoL in Adult Cancer Survivors Survey, consisting of 47 items on a 7‐point frequency scale. Data were analysed using both descriptive statistical models and adjusted multivariate logistic regression. Results There were 677 respondents generating a 61% response rate. Overall, higher stage at diagnosis correlated with the largest decreases in QoL as it pertained to both general (p = 0.001) and Cancer‐Specific stressors (p < 0.001). Education level (p = 0.020), age (p < 0.001), rural area code designation (p = 0.020) and family history of melanoma (p = 0.017) were also independently associated with changes in QoL. Conclusion Earlier stage at melanoma diagnosis is associated with better QoL and thus represents a crucial intervention in patient care. Given our findings and the growing body of evidence surrounding morbidity in late‐stage melanoma, it is essential that QoL be included in assessing the benefits of early detection.